Polyphyllin I Mitigated IL-1β-Induced Chondrocytes Damage through Downregulating TWIST1 Expression - Liu, Feng; Han, Bowen; Yang, Deshun; Ji, Xiaopeng; Yan, Liangliang; Han, Chaoyong (Current Molecular Medicine, 2025)
BackgroundOsteoarthritis (OA) is a chronic joint disease characterized by the degradation of articular cartilage. Polyphyllin I (PPI) has anti-inflammatory effects in many diseases. However, the mechanism of PPI in OA remains unclear.MethodsHC-a cells treated with IL-1β were identified by immunofluorescence staining and microscopic observation. The expression of collagen II and DAPI in HC-a cells was detected by immunofluorescence. The effects of gradient concentration of PPI on IL-1β-induced cell viability, apoptosis, senescence, and inflammatory factor release were detected by MTT, flow cytometry, SA-β-Gal assay and ELISA, respectively. Expressions of apoptosis-related genes, extracellular matrix (ECM)-related genes, and TWIST1 were determined by qRT-PCR and western blot as needed. The above-mentioned experiments were conducted again after TWIST1 overexpression in IL-1β-induced chondrocytes.ResultsIL-1β reduced the number of chondrocytes and the density of collagen II. PPI (0.25, 0.5, 1 μmol/L) had no effect on cell viability, but it dose-dependently elevated the inhibition of cell viability regulated by IL-1β. The elevation of cell apoptosis, senescence and expression of IL-6 and TNF-α were suppressed by PPI in a dose-dependent manner. Additionally, PPI reduced the expression of cleaved caspase-3, bax, MMP-3, and MMP-13 and promoted the expression of collagen II. TWIST1 expression was diminished by PPI. TWIST1 overexpression reversed the above-mentioned effects of PPI on chondrocytes.ConclusionPPI suppressed apoptosis, senescence, inflammation, and ECM degradation of OA chondrocytes by downregulating the expression of TWIST1.
Keywords: Osteoarthritis